Propuesta de un sistema de control de inventarios para la empresa Distribuciones León (2022)
Obtaining profits lies in the generation of sales, since they are the engine of any company. However, if inventory management is not operating effectively, you may not be able to meet the demand for the product. This situation can cause the dissatisfaction of a client, who will opt for a competitor, which will result in the loss of profits and the credibility of the organization. The present work is carried out to respond to the problem presented in the company Distribuciones León in the city of Villavicencio/Meta, which immediately requires the implementation of an inventory control system, based on concise strategies that allow real records to be kept. and efficient. The different causes and effects produced by the lack of an inventory control system in the organization are analyzed; This study is carried out from inside the company, with full knowledge of the different areas and the actors involved in each one, conducting interviews on how the performance of each collaborator affects the company's activities. During the analysis it was observed that the problems stemmed from not having a concise answer when asked about a product in the warehouse, and from the operational time wasted trying to keep an empirical count of product inputs and outputs, in addition, there were losses of merchandise, delayed enlistment processes, lack of communication in dispatch, returns, poor purchasing practices, this being a consequence of the absence of inventory control. As a result of the analysis, an inventory control model is proposed from the Excel program, which is composed of 4 modules (entries, inventory, sales and graphical representation). The advantages of this proposal establish that costs related to the problems mentioned above are optimized, in addition, it proposes to carry out a control based on the ABC method, which will allow relating low rotation products and offers the possibility of having real tonnage of inputs and outputs.